Self-reported hearing measures can predict risk of falling and balance problems - Hanna Putter-Katz; Niza Horev; Erez Yaakobi; Ella Been (Communications Medicine)
Abstract Introduction Falls in the elderly are a major source of injury that can result in disability and hospitalization. Early detection of balance deterioration and the risk of falling is thus crucial to preventive care. Older adults with hearing loss are 2.4 times more likely to experience falls than their normal-hearing peers. This study explored the utility of a self-reported hearing measure (The Amsterdam Inventory for Auditory Disability and Handicap—AIADH) as a predictor of balance problems and the risk of falling. Methods A sample of 148 individuals (18–90 years) completed two objective hearing tests (Standard Pure-Tone Audiometry and Words-in-Noise), one self-reported hearing inventory—AIADH, one balance test—Timed Up and Go, and the Activity-Specific Balance Confidence Scale that self-reports balance. The analysis included correlation and regression analyses, moderation, sensitivity, and specificity analyses. Results The findings suggest that AIADH constitutes a good predictor of a decline in balance and an increased risk of falling, which complements objective hearing measures in adults aged forty and over. Prediction accuracy rises with age. The findings also reveal that out of all the AIADH subscales, the detection subscale is the best predictor of balance problems and risk of falling. Conclusions Thus, using an available self-report hearing inventory can be a useful and potentially cost-effective tool for the early detection of balance problems and hearing deterioration. Health authorities should consider incorporating this type of evaluation as a remote screening tool for large populations at risk.